A phenomenological study of psychotherapy: a client explicates his experience - Frank, Anthony Ernest (Rhodes University, Faculty of Humanities, Department of Psychology, 1982)
From Introduction: This thesis involves a detailed explication of my experience as a client in psychotherapy. Being in therapy has brought about extremely important ·changes in my life and continues to do so. Being involved · in the field of· psychology as a student and therapist-to-be, the experience of therapy has also been a valuable source of a greater understanding of the process itself. The various facets of the importance of my experience of psychotherapy will become clear in my explication. It is a fact that experience, which is an essential aspect of our humanness, has been sadly neglected in psychological research. It is surely psychology's task to explore all aspects of humanity, and this neglect of experience has only fairly recently been questioned. Its reasons have been psychology's bias towards the natural sciences whose methods are not suitable for the study of experience. The tremendous achievements of the natural sciences caused psychology to adopt this slant, as Sigmund Koch (19.69) puts it, "The stipulation that psychology be adequate · to science outweighed the commitment that it be adequate to man". (p 65).
Keywords: Psychotherapy -- Research; Insight in psychotherapy; Psychotherapy -- Case studies; Psychotherapy patients